2008
DOI: 10.14429/dsj.58.1644
|View full text |Cite
|
Sign up to set email alerts
|

Perforated Plates as Passive Mitigation Systems

Abstract: This paper presents the results of tests on fully-clamped circular plates subjected to blast loading directed down a tube. Four series of tests were performed. In one set of experiments, the blast wave was allowed to progress unhindered down the tube to impinge upon the plate, and in the other tests, perforated plates were placed in the path of the blast wave to hinder progression down the tube, disrupting the blast and absorbing some of the kinetic energy. Results of the tests indicate that the perforated pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…The highest attenuation was obtained with the grid having the lowest porosity. Langdon et al [13] have observed the mitigation capacity of perforated plates on plates fully clamped to blast loading directed down a tube. The influence of a mild steel plate's thickness and hole size on its response to blast loading has been also studied [14].…”
Section: Introductionmentioning
confidence: 99%
“…The highest attenuation was obtained with the grid having the lowest porosity. Langdon et al [13] have observed the mitigation capacity of perforated plates on plates fully clamped to blast loading directed down a tube. The influence of a mild steel plate's thickness and hole size on its response to blast loading has been also studied [14].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore DP and TRIP steels have high impact strength and they can be used for perforated steel armour. Because perforated plates are also attractive for passive mitigation systems against explosive blast [24]. In this study, it was aimed to investigate the metallurgical structure of the weld zone (FZ), strength values such as hardness, tensile strength, toughness and elongation percentages of the welded parts by similar combining TRIP 800 and DP 1000 steels with the EBW welding method.…”
Section: Introductionmentioning
confidence: 99%
“…Solutions proposed for attenuation and reflection of shock waves and high-energy flows included use of permeable solids, porous materials, and solid geometric reflectors. 4 Various media that have been used in research include energy-absorbing or energy-dissipating foams, 5 liquids encapsulated in elastic shells, textiles, cellular materials, resin-bonded aggregates, honeycomb structures, 6 perforated plates, 7 and granular media.…”
Section: Introductionmentioning
confidence: 99%